2021
DOI: 10.17306/j.afs.0857
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleracea Mart.) reduces the inflammatory response triggered in vitro by the antipsychotic drug olanzapine in RAW 264.7 macrophage cells

Abstract: Background. Açaí (Euterpe oleracea Mart), a Brazilian fruit, is considered a "superfruit" due its energetic properties and bioactive compounds. The açai's anti-inflammatory effects could attenuate the undesirable metabolic and pro-inflammatory side effects triggered by some antipsychotic drugs, such as Olanzapine (OLZ). It is possible to infer that açai supplement could potentially minimize the adverse effects of OLZ. Aim. This study tested the potential in vitro effects of açai hydroalcoholic extract on the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For example, previous investigations carried out by our research team showed that Rotenone-induced mitochondrial dysfunction could be reversed in the presence of açai extract, an Amazon fruit with antioxidant and anti-inflammatory action [33]. Likewise, açai was able to reverse the inflammatory activation of macrophages [49] and microglia [50]. Other studies have also shown that the inflammatory pattern associated with the VV-SOD2 genotype was attenuated in vitro by supplementing cell cultures with lithium [51].…”
Section: Discussionmentioning
confidence: 65%
“…For example, previous investigations carried out by our research team showed that Rotenone-induced mitochondrial dysfunction could be reversed in the presence of açai extract, an Amazon fruit with antioxidant and anti-inflammatory action [33]. Likewise, açai was able to reverse the inflammatory activation of macrophages [49] and microglia [50]. Other studies have also shown that the inflammatory pattern associated with the VV-SOD2 genotype was attenuated in vitro by supplementing cell cultures with lithium [51].…”
Section: Discussionmentioning
confidence: 65%